The Multifaceted Neurotoxicity of Astrocytes in Ageing and Age-Related Neurodegenerative Diseases: A Translational Perspective - Bouvier, David S.; Fixemer, Sonja; Heurtaux, Tony; Jeannelle, Félicia; Frauenknecht, Katrin B. M.; Mittelbronn, Michel (Frontiers in Physiology, 2022)
In a healthy physiological context, astrocytes are multitasking cells that contribute to the central nervous system (CNS) homeostasis, to its defence and immunity. In cell culture or rodent models of age-related neurodegenerative diseases (NDDs), such as Alzheimer’s disease (AD) and Parkinson’s disease (PD), numerous studies have shown that astrocytes can adopt neurotoxic phenotypes that could exacerbate disease progression. Chronic inflammatory responses, oxidative stress, unbalanced phagocytosis, or alteration of their core physiological roles are the main manifestations of their detrimental states. However, if astrocytes are directly involved in brain deterioration by exerting neurotoxic functions in patients with NDDs is still controversial. The large spectrum of NDDs, with often overlapping pathologies, and the technical challenges associated with the study of human brain samples complexify the analysis of astrocyte involvement in specific neurodegenerative cascades. With this review, we aim to provide a translational overview about the multi-facets of astrocyte neurotoxicity ranging from in vitro findings over mouse and human cell-based studies to, rodent NDDs research and finally evidence from patient-related research. We also discuss the role of ageing in the astrocyte encompassing changes in physiology and response to pathologic stimuli and how this may prime detrimental responses in NDDs. To conclude, we discuss how potentially therapeutic strategies could be adopted to alleviate or reverse astrocytic toxicity and their potential to impact neurodegeneration and dementia progression in patients.